Pendampingan Pembentukan Kelembagaan dan Komunikasi Waria Crisis Center (WCC) - Putra, Tegar Satya; Listiorini, Dina (Jurnal Atma Inovasia, 2022)
The Transgender women community in Indonesia is considered an underprivileged community due to the social and systemic exclusion they experience daily. This condition is worsened due to COVID-19. Due to the pandemic, many transgender women cannot do their job to finance their daily needs to Mass Mobility Restrictions. They also do not have access to vaccines and clinical treatment because most do not have an ID card or social security numbers. To tackle the escalated problem, the transgender women community in Jogjakarta, Indonesia, through Waria Crisis Center (WCC) initiates philanthropic activity to help transmen who suffer health or financial crises. UAJY community service team tries to support WCC in two areas. First, we help WCC to develop its social media presence by helping them setting WCC Instagram dan Facebook official accounts. Second, we help WCC to establish good organizational practice by helping WCC to establish formal job descriptions and report flow.